Reimagining Indigenous Education in Costa Rica through Paulo Freire’s Pedagogical Lens: A Critical Analysis: Reimaginar la educación indígena en Costa Rica a través de la lente pedagógica de Paulo Freire: un análisis crítico - Bernard, Dianala (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2024)
The present research analyzes Paulo Freire's renowned work Pedagogy of the Oppressed within the context of education for Costa Rica’s Indigenous populations. It critically examines Costa Rican education and its role in perpetuating or challenging oppression in Indigenous populations. Freire argues that traditional models of education, where teachers impart information to passive students, serve to maintain the status quo and oppress the marginalized, such as Indigenous communities. Instead, he proposes a problem-posing approach that encourages critical thinking, dialogue, and collective action to transform unjust realities. Emphasizing the examination of the possible impact of Freirean pedagogy on Indigenous culture, language, socialization, Social and Emotional Learning (SEL), and Culturally Responsive Pedagogy (CRP), the present study explores the complexities of educational theory and practice for Indigenous populations in Costa Rica. In examining how Freire's pedagogical principles intersect with Indigenous populations' unique challenges and opportunities, this analysis aims to inform policy and practice toward educational equity and social justice for Costa Rica’s eight Indigenous populations.